Indian muftis and the non-Muslims - Baljon, Johannes Marinus Simon (Islam and Christian-Muslim relations, 1991)
Muslims like to emphasize that Islam represents primarily a way of life and not a system of belief with elaborate doctrines. This statement is justified by the discussions of Indian jurisconsults about the attitudes to be taken towards non-Muslims. It is true that they occasionally engage in a polemic concerning theological issues, but the main concern is directed towards practical problems the ordinary believer is faced with in his relations with non-Muslims. Consequently, most fatwas in this context deal with day-to-day worries. The trouble caused by Hindus is the allurement of their exuberant festivals and imaginative rituals, whereas questions raised in regard to the British stem from uneasy feelings roused by the strangeness of European culture and its fashions.